“Effectiveness of Cold Needle to Administer Intramuscular Injection on Pain Perception among Adult Patients” - Ms. Nisha Kamble; Mr. Amos Talsandekar; Mrs. Neeta Ranbhise (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives. Injections are among the most commonly performed medical procedure in a hospital. The uncomfortable sensation caused by pain from intramuscular injection should not be trivialized, because a painful injection could create neurotic fear of the injection and may even delay a patient from seeking treatment. According to the WHO, around 16 billion injections administered globally each year. In India, prevalence of intramuscular injection range is between 0.9-8.5 injections per person per year. A community survey reported that 27.1% of the subject’s received injections. A challenge for the nurse is to administer painless injection to help alleviate pain, particularly for patients who fear needles and injection. The “Cold needle” technique is one such method, which can be used to provide painless intramuscular injection. The researcher aims to evaluate the effectiveness of cold needle to administer Intramuscular Injection on pain perception among adult patients at Dr. D.Y. Patil Medical College Hospital and Research Centre, Kolhapur. The study seeks to understand the Pain perception of adult patients receiving intramuscular injection and identify ways to support them. Objectives: The present study is aimed that to evaluate the effectiveness of cold needle to administer intramuscular injection on pain perception among adult patients at Dr. D. Y. Patil Medical College Hospital and Medical Research centre, Kolhapur. The objectives are as follows, 1. To evaluate the effectiveness of cold needle to administer intramuscular injection on pain perception among adult patients within experimental group. 2. To compare the mean post-test pain perception score of adult patients between experimental group and control group. 3. To find out an association between post-test pain perception score and selected socio-demographical variables in control group and experimental group. Methods: A quantitative research approach was adopted for the study. A quasi-experimental post-test only control group design was chosen. By using non-probability purposive sampling technique 50 adult patients (aged 21-60 years) receiving IM injection was selected. The experimental group received IM injection with a needle cooled to 2-8 degree Celsius for 1 minute, while the control group received routine room-temperature injections. Pain was assessed using the Visual Analogue Scale (VAS). Data were analyzed with descriptive statistics Mean, Median, Mode, Range, Standard deviation, Unpaired t-test, and Chi-square test. Result: The study finding revealed that in experimental group, 56% no pain, 36% had mild pain and 8% having moderate pain while receiving intramuscular injection. In control group, 60% reported mild pain, 32% had moderate pain and 8% had no pain. Mean pain score after intervention in experimental group is 1.04 ± 1.3 and the mean pain score without intervention in control group is 2.60 ±1.2 which was found to be significant at p<0.05 level with ‘t’ value is 4.14. Hence cold needle is effective to reduce pain perception. There was significant association found between age and pain score in experimental group (p<0.05). Interpretation and conclusion: The study concludes that the level of pain perception among adult patients receiving Intramuscular injection at Dr. D.Y. Patil medical college hospital and research centre, Kolhapur. In this study majority of respondents (56%) experienced no pain in experimental group than in control group. The finding of this study suggests that using cold needle for intramuscular injection significantly reduces pain perception among adult patients compare to room temperature needle. This simple and cost-effective technique can be easily implemented in clinical settings to enhance patient comfort and reduce injection related anxiety.